Regenerative braking system (Rbs) mosfet switching-based drive cycle for an electric motorcycle - Mohd Noor, Nurul Muthmainnah; Toha, Siti Fauziah; Abdullah, Muhammad; Ahma, Salmiah; Rahman, Md Ataur (International Islamic University Malaysia-IIUM, 2025)
A regenerative braking system is an advanced technology applicable to transportation, particularly electric vehicles. The purpose of incorporating regenerative braking is to recover energy during braking and deceleration, which can be stored in the battery. This paper aims to study the operation of the regenerative braking system based on an urban drive cycle. This study selects the US60 and NEDC drive cycles as inputs to evaluate future powertrain systems and vehicle concepts. The output torque is calculated longitudinally based on the vehicle dynamic equation to determine whether the torque is negative or positive. When the torque is negative, regenerative braking applies, and the state of charge (SoC) of the battery increases. The concept of regenerative braking is that this system uses four MOSFETs as switches. As a result, at the 50% level of SoC, the first regeneration improved performance by 12.22%, whereas the second showed a smaller gain of 5.96%. Similarly, at the 80% level of SoC, the first regeneration yielded a 12.55% increase, while the second achieved only a 6.19% improvement. The rise in SoC for both levels demonstrates that energy can be recovered when implementing regenerative braking. Therefore, the results obtained from the MATLAB simulation will be used for future studies in implementing a regenerative braking control strategy.